2010
DOI: 10.1242/jeb.036277
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia-induced Hsp70 and MT20 transcriptional upregulation are mediated by p38-MAPK and JNKs inMytilus galloprovincialis(Lamarck); a pro-survival response

Abstract: SUMMARYIn the present study we investigated the signal transduction cascades triggered by acute thermal stress in Mytilus galloprovincialis gills. This particular species has been reported to exhibit a significant tolerance to high temperatures; thus, it was intriguing to examine the molecular mechanisms responsible for this extraordinary trait. In particular, exposure to 30°C was found to cause a significant and sustained stimulation of p38-MAPK phosphorylation while the activation profile of JNKs was transie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 57 publications
1
32
1
Order By: Relevance
“…Our results showed that phospho-p38-MAPK levels increased significantly in hemocytes of M. galloprovincialis at 28°C; however, there was no significant change in hemocytes of M. californianus under this condition. Similarly, exposure to high temperature was found to cause a significant and sustained stimulation of p38-MAPK phosphorylation in the gill tissue of M. galloprovincialis (Gourgou et al, 2010;Kefaloyianni et al, 2005). Our results indicate that M. californianus might lose this component of the cellular stress response at temperatures of 28°C and higher, whereas M. galloprovincialis retains this ability.…”
Section: Stress-signaling Proteinsmentioning
confidence: 51%
See 3 more Smart Citations
“…Our results showed that phospho-p38-MAPK levels increased significantly in hemocytes of M. galloprovincialis at 28°C; however, there was no significant change in hemocytes of M. californianus under this condition. Similarly, exposure to high temperature was found to cause a significant and sustained stimulation of p38-MAPK phosphorylation in the gill tissue of M. galloprovincialis (Gourgou et al, 2010;Kefaloyianni et al, 2005). Our results indicate that M. californianus might lose this component of the cellular stress response at temperatures of 28°C and higher, whereas M. galloprovincialis retains this ability.…”
Section: Stress-signaling Proteinsmentioning
confidence: 51%
“…Gill tissue of M. galloprovincialis (Gourgou et al, 2010) and mantle tissue and posterior adductor muscle of both M. galloprovincialis and M. barbatus also showed activation of JNK at high temperature (Anestis et al, 2007;Anestis et al, 2008), suggesting a common cellular stress response to heat stress in different cell types of these two mussels. The results of the present study showed that both cold and heat stress induced a significant increase in JNK phosphorylation in hemocytes of M. galloprovincialis, with the strongest expression at 28°C.…”
Section: Stress-signaling Proteinsmentioning
confidence: 94%
See 2 more Smart Citations
“…A new method to treat malignant glioma by thermotherapy has been used for patients with malignant glioma (Du et al, 2009). Thermotherapy is a comprehensive treatment that is gradually being recognized by clinicians; it has a characteristically precise role and has no known side effects (Iwasaki et al, 1993;Ivarsson et al, 2003;Gourgou et al, 2010;James et al, 2010). Increasing evidence suggests that there is an evident decrease in both tumor surgical relapse rate and mortality following thermotherapy treatment (Jurivich et al, 1995).…”
Section: Introductionmentioning
confidence: 99%